Analisis Marketing Mix Menggunakan Triangulasi Method Pada Pt Lembimjar Neutron Yogyakarta Cabang Tamansiswa - Fernina Putri Wulandari; Indah Kurniawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Many strategies can be used to increase sales volume, one of them is marketing mix. This study aims to determine whether the marketing strategy implemented by PT Lembimjar Neutron Yogyakarta Tamansiswa Branch is appropriate and can increase sales volume. This research uses descriptive qualitative research methods. The researcher took an object at a service company, namely PT Lembimjar Neutron Yogyakarta Tamansiswa Branch, which is located on Jl. Tamansiswa, No.96, Wirogunan, Yogyakarta Special Region. This research was conducted on November 5, 2022 - December 10, 2022. The data collection techniques used in this research are interviews and observations. The results of this study indicate that the strategy used by PT Lembimjar Neutron Yogyakarta Tamansiswa Branch uses 7P (product, price, place, promotion, people, physical evidence, and process). Products sold with a variety of school levels and there are special Alumni products. Affordable price. The location used is strategic. Promotion uses various platforms and direct promotion is also carried out. Has staff who are experts in their fields. Adequate facilities and the process of being able to join Neutron is very easy. Keywords: Strategy, Marketing Mix